Many happy returns! An exploration of the socio-economic background and access experiences of those who (re)turn to part-time higher education. Issue 1 (2nd January 2020) - Delaney, Lorraine; Brown, Mark
Abstract : While access to higher education (HE) has substantially increased over the past number of years, the evidence suggests that social inequalities continue to be reproduced in terms of course level, field of study and institutional status. This paper examines, through the lens of Social Reproduction Theory, the socio-economic background and HE access experiences of those ( n  = 268) who recently completed a University undergraduate honours degree, part-time. Mixed methods of data collection are employed including an analysis of institutional documents, an online survey (126 respondents) and 17 semi-structured interviews. The literature tells us that adults delay their participation in HE, often for reasons relating to social class, and are more likely to participate part-time. Contrary to the existing literature, this paper outlines how adults have not necessarily delayed their participation in HE. Rather, they participate in HE incrementally from the time they leave school, often on a part-time basis. Instead of delayed participation, working-class students' participation in HE is regularly protracted, most often for reasons relating to social class. This paper identifies a potentially new conceptualization of the part-time student as one who participates regularly and incrementally on completion of compulsory education, in order to enhance their qualification level.